Atmospheric air quality in Beijing improved by application of air source heat pump (ASHP) systems. (1st June 2020) - Xu, Zhaowei; Liu, Fang; Xu, Wei; Wang, Zhichao; Yang, Yingxia; Xu, Ce; Wu, Pin; Li, Xiaofeng
Abstract: In order to prevent the pollution emission of extensive coal burning, Beijing government has accelerated the transformation of coal into electricity, and established a clean energy system. Herein, the actual operating efficiency of 50 air source heating pump (ASHP) systems was investigated during the heating season in 2016–2018. The results showed that the indoor temperature could meet the demands of the indoor thermal comfort of rural residents. Correspondingly, the coefficient of performance (COP) value of the typical day was 2.07 and 2.24, respectively. The primary energy utilization rate exceeded 79%, which shows good applicability and had obvious energy-saving effect. Moreover, the relationship between the renewable energy and air quality was discussed. The atmospheric air quality was improved year by year by comparison of the air quality before and after the ASHP usage. It found that the effect of pollutant emission reduction by ASHP system has a strong impact on the reduction of PM10 and PM2.5 concentration (absolute Pearson's r : 0.6525 and 0.6128) by correlation analysis. Therefore, the application of ASHP system has made a great contribution to the air quality improvement during the year of 2016–2018, which contributed an important force to the clean heating of northern China. Highlights: The primary energy utilization rate of ASHP system exceeded 79%, which had obvious energy-saving effect. The atmospheric air quality was improved year by year by comparison of the air quality before and after the ASHP usage. The pollution reduction of SO2, NO2 and particle matter were 25.07%, 0.77% and 17.75% in the 2017, respectively. The contribution of clean energy replacement on emission reduction of PM10 is greatest, following by PM2.5, SO2, and NO2 .